Production of naturally ‘‘lactose free” fresh cheese” (Research, Society and Development, 2020)
Lactose intolerance is a disorder that affects a large part of the population, in this sense, it becomes feasible the study of manufacturing techniques that make it possible to guarantee the elaboration of products with low lactose content. Taking this into account, the present study aimed to evaluate the lactose content and physical-chemical characteristics of washed mass cheeses during the maturation period. Pasteurized whole milk with initial lactose percentage of 4.55 g/100 g was used and after coagulation, cutting and stirring, a partial (10% of the initial volume) whey removal was followed by addition of the same volume of hot water at 75 °C. Cheeses were analyzed at 0, 7, 15, 30 and 60 days of maturation for lactose content, acidity, pH, water activity, moisture, fixed mineral residue and chlorides. A lactose content of less than 0.005 g/100 g was obtained shortly after manufacturing (fresh product). The starter culture used and the process of washing the mass likely contributed to the low lactose content of the cheeses. Thereby is presented a viable alternative for the production of naturally lactose-free cheeses.